Accelerated Life Test and FEM Simulation-Based Fatigue Analysis of an Aluminum Alloy Push Rod - Xua, L.; Dai, G.Z. (Проблемы прочности, 2019)
The accelerated life test based on the spectrum of fatigue loads was used both in numericalsimulation and bench tests of the push rod. The symmetrical cycling of the push rod was presented asthe positive pulsating load spectrum corresponding to the stress spectrum of the critical node in thefinite element model. As FEM analysis demonstrates, the fatigue crack initiation would occur at theedge of the first-position pin hole with maximum stress and minimum fatigue life. Bench test results show that the fatigue crack initiation and fatigue life of the push rod are in good agreement with FEM data.